Sulfation Pathways During Neurodevelopment - Clarke, Taylor; Fernandez, Francesca E.; Dawson, Paul A. (Frontiers in Molecular Biosciences, 2022)
Sulfate is an important nutrient that modulates a diverse range of molecular and cellular functions in mammalian physiology. Over the past two decades, animal studies have linked numerous sulfate maintenance genes with neurological phenotypes, including seizures, impaired neurodevelopment, and behavioral abnormalities. Despite sulfation pathways being highly conserved between humans and animals, less than one third of all known sulfate maintenance genes are clinically reportable. In this review, we curated the temporal and spatial expression of 91 sulfate maintenance genes in human fetal brain from 4 to 17 weeks post conception using the online Human Developmental Biology Resource Expression. In addition, we performed a systematic search of PubMed and Embase, identifying those sulfate maintenance genes linked to atypical neurological phenotypes in humans and animals. Those findings, together with a search of the Online Mendelian Inheritance in Man database, identified a total of 18 candidate neurological dysfunction genes that are not yet considered in clinical settings. Collectively, this article provides an overview of sulfate biology genes to inform future investigations of perturbed sulfate homeostasis associated with neurological conditions.